Implication and evaluations of indoor soot particles from domestic fuel energy sources using characterization techniques in northern Pakistan. Issue 12 (21st July 2021) - Bibi, Shah Dehrai; Baig, Shams Ali; Zeb, Iftikhar; Ali, Maroof; Shams, Dilawar Farhan; Nawab, Javed; Yosifova Aneva, Ina; Hussain, Hidayat; Xu, Xinhua
Abstract: Soot particles emitted from the burning of solid fuel sources in the households carry important environmental and public health implications. In this study, the indoor soot particles released from firewood, cow dung, and bagasse burning at households of selected rural areas of Khyber Pakhtunkhwa province of Pakistan were investigated by characterization analyses to study its morphological and elemental compositions. Results demonstrated diverse compositions of soot particles from each fuel source. The surface areas of soot particles emitted by the firewood, cow dung, and bagasse were about 0.3, 0.4, and 8.64 m 2 g −1, respectively. For the soot particles emitted by the firewood burning, the major functional groups for aromatic compounds were C═C at the 1, 431–1, 599 at 1, 000–2, 000 cm −1 . The absorbance rate of alkanes was about 1, 599–1, 431 at 1, 000–2, 000 cm −1 . However, silicon band vibration was more prominent in bagasse soot particles as compared to other samples. The emission of soot particles with high surface area in the atmosphere could provide an elevated adsorption sites for atmospheric pollution and trap more energy resulting in increased atmospheric temperature. Findings from the present study suggest that current households' fuel combustion practices significantly contribute to increase the particulate matter in the atmosphere and possible enhance climate change phenomenon and related disasters in northern Pakistan. Abstract : Domestic fuel sources burning releases soot particles create environmental and public health concerns. Soot particles generated from the burning of different domestic fuel sources were studied. Characterization tests revealed of diverse compositions among the samples.